Molecular biomarkers of DNA damage in diffuse large-cell lymphoma—a review - Ruhe, Madeleine; Rabe, Dominik; Jurischka, Christoph; Schröder, Julia; Schierack, Peter; Deckert, P. Markus; Rödiger, Stefan (Journal of Laboratory and Precision Medicine; Vol 4 (February 2019): Journal of Laboratory and Precision Medicine, 2019)
Diffuse large B-cell lymphoma (DLBCL) is a highly aggressive form of non-Hodgkin’s lymphoma with a long-term survival rate of around 60% upon standard treatment with rituximab and chemotherapy. While this marks a great improvement over the pre-rituximab/pre-biologicals era, DLBCLs remain a heterogeneous disease with marked variability in clinical outcome. Efforts have been undertaken to predict its course based on characteristics such as the activated B-cell (ABC) versus germinal centre B-cell (GCB) types, but so far none of these has had much impact on treatment and outcome, and the international prognostic index, based on clinical and basic laboratory features, remains the best risk predictor. This review focuses on 13 biomarkers that have been described in the context of diagnostic tests, clinical studies or basic research related to solid and haematological malignancies in general or DLBCL in particular. These include biomarkers of the DNA repair response such as the phosphorylated histone variant 2AX (γH2AX), p53 binding protein (53BP1), Ataxia telangiectasia mutated protein (ATM), Ataxia telangiectasia and Rad3-related protein (ATR), the DNA-dependent protein kinase (DNA-PK) and Rad51 as well as proto-oncogene products like Myc, B-cell lymphoma 2 (Bcl-2), breast cancer 1 (BRCA1) and signal transducer and activator of transcription 3 (STAT3). We have also included 8-Hydroxy-2'-desoxyguanosine (8-OHdG), a marker for oxidative stress, and discuss a link between two proteins involved in apoptosis, the proteasome activator 28γ (PA28γ) and tumour suppressor p53. Our investigation revealed a connection between almost all biomarkers, which are based on methods such as indirect immunofluorescence, fluorescence in-situ hybridization or immunohistochemistry.